Pengaruh Pengetahuan dan Keterampilan terhadap Kinerja Pegawai Dinas Pariwisata - Rosdiana Tajuddin; Hendrik Hendrik; Fitri Kumalasari; Andry Stepahnie Titing (Jurnal Ekonomi & Bisnis, 2023)
This study aims to determine whether there is the effect of knowledge and skills on employee performance at the tourism office of kolaka district. The sample in this study amounted to 55 respondents using a sampling technique, namely the census method. Testing the research instrument using validitiy test and reliability test with SPSS 22.0. The research data analysis technique uses the Structural Equation Modeling (SEM-PLS) method with SmartPLS 4.0. Based on the results of this study, it can be seen that the knowledge variable has no effect on performance as indicated by the T-Statistik Value of 0.291 and P-Values of 0.386 an the skill variabel shas a positive ang significant effecect on performance as indicated by the T-Statistic value of 6.497 and P-Values 0.000.